UNDERSTANDING POLYSEMY IN LANGUAGE (Ustozlar uchun, 2026)
This article deals with “Leksikologiya” the Uzbek folklore in teaching young learnersand  using  interactive  ways  of  conducting  sessions.  Key  words:  functional literacy, reading literacy, pedagogical technologies, texttechnology, methodical.